2006
DOI: 10.1002/jor.20197
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell‐derived factor 1 (SDF‐1, CXCL12) is increased in subacromial bursitis and downregulated by steroid and nonsteroidal anti‐inflammatory agents

Abstract: Several studies have demonstrated that inflammation in the subacromial bursa is an important component in the pathogenesis of impingement syndrome. We have demonstrated in a previous study that many inflammatory cytokines, including stromal cell-derived factor 1 (SDF-1, CXCL12), are increased in the subacromial bursa [Blaine et al. 2005. J Shoulder Elbow Surg 14(Suppl 1):84S-89S]. SDF-1 is a potent chemotactic and angiogenic factor that stimulates recruitment of inflammatory cells. In the current study, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
2
29
2
Order By: Relevance
“…Corticosteroid application in primary CNS lymphoma patients might have biased our results because of the downregulation of chemokine expression (26,27), However, we did not find an impact of corticosteroid pretreatment on CSF chemokines levels. Serum CXCL12 levels were somewhat lower in corticosteroid pretreated patients, which possibly reflects the anti-inflammatory properties of corticosteroids.…”
Section: Discussioncontrasting
confidence: 72%
“…Corticosteroid application in primary CNS lymphoma patients might have biased our results because of the downregulation of chemokine expression (26,27), However, we did not find an impact of corticosteroid pretreatment on CSF chemokines levels. Serum CXCL12 levels were somewhat lower in corticosteroid pretreated patients, which possibly reflects the anti-inflammatory properties of corticosteroids.…”
Section: Discussioncontrasting
confidence: 72%
“…One study found that hypoxic conditions in the synovium of rheumatoid arthritis may induce production of SDF-1, contributing to the persistence of synovitis [40]. Other recent studies showed that interleukin-1 appears to induce SDF-1 expression in human subacromial bursa [41], and that SDF-1 expression in bursal cells can be inhibited by steroid and nonsteroidal antiinflammatory agents [42]. These studies suggest that SDF-1 levels are likely associated with the progression of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, administration of dexamethasone and a COX-2 inhibitor decreases SDF-1 production associated with subacromial bursitis. 44 Therefore, it is likely that if any of the horses in the present study received intra-articular injections of corticosteroids prior to surgery, SDF-1 production in the affected joint would decrease. However, in another equine study 45 in which medication history was known, it was concluded that medication effects on biomarkers were not straightforward because the duration of effects of commonly used medications administered intra-articularly are not well documented.…”
Section: Discussionmentioning
confidence: 89%